A genetic linkage map of the hermaphrodite teleost fish Sparus aurata L. - Bargelloni, L. (2018)
The gilthead sea bream (Sparus aurata L.) is a marine fish of great importance for fisheries and aquaculture. It has also a peculiar sex-determination system, being a protandrous hermaphrodite. Here we report the construction of a first-generation genetic linkage map for S. aurata, based on 204 microsatellite markers. Twenty-six linkage groups (LG) were found. The total map length was 1241.9 cM. The ratio between sex-specific map lengths was 1:1.2 (male:female). Comparison with a preliminary radiation hybrid (RH) map reveals a good concordance, as all markers located in a single LG are located in a single RH group, except for Ad-25 and CId-31. Comparison with the Tetraodon nigroviridis genome revealed a considerable number of evolutionary conserved regions (ECRs) between the two species. The mean size of ECRs was 182 bp (sequence identity 60–90%). Forty-one ECRs have a known chromosomal location in the pufferfish genome. Despite the limited number of anchoring points, significant syntenic relationships were found. The linkage map presented here provides a robust comparative framework for QTL analysis in S. aurata and is a step toward the identification of genetic loci involved both in the determination of economically important traits and in the individual timing of sex reversal.